Human Recognition Based on the Depth Image in Rail Vehicle - TONG Lu; SHEN Ping; WANG Li-de; LIU Ming-kun (机车电传动, 2014)
A method based on depth image local normal vector characteristic, described by spherical coordinate parameters ( , ), was proposed in this paper and suited to rail vehicle with the high-density passengers. This method implemented the human recognition by capturing the local normal vector, and then extracting the head contour. Depth image was a better way to solve the limitations of environmental factors effectively, such as height and illumination. Finally, some experiments were taken to test and verify the real-time performance and accuracy.